Transient pool boiling and particulate deposition of copper oxide nano-suspensions. (July 2020) - Li, Zhixiong; Mazinani, A.; Hayat, Tasawar; Al-Rashed, Abdullah A.A.A.; Alsulami, H.; Goodarzi, Marjan; Sarafraz, M.M.
Highlights: This is a study on the potential effect of nanoparticle fouling on surface characteristics. Nanomaterial samples are characterised by SEM, EDX and nanoparticle sizer. Effect of surface characteristics on boiling performance of CuO-water is studied. Bubble formation, surface roughness, contact angle and departure time are measured. Study was categorised into two domains of steady state and transient measurements. Abstract: In the present work, we report the results of series of experiments aiming at identifying the key mechanisms affecting the transient boiling heat transfer coefficient. Two categories of experiments were designed and conducted in which the heat transfer coefficient and fouling thermal resistance were quantified at steady state condition and in a transient study over 1000 min of continuous operation of the heater. CuO-water nano-suspension was prepared, stabilised and used with the view to improve the thermal conductivity of water and thereby increasing the heat transfer coefficient. Results showed that at initial times of the experiments, the heat transfer coefficient was improved due to the increase in the thermal conductivity of the nano-suspension, and the emerge of some micro-scale phenomena such as Brownian motion and thermophoresis effect. While over 1000 min of continuous measurement, it was identified that the heat transfer coefficient was suppressed due to the formation of the fouling layer. Thermal resistance induced by the fouling layer together with the heat accumulation on the surface, a decrease in surface roughness value and also the suppression of the rate of the bubble formation were the main contributors that decreased the transient thermal performance of the system. It was also identified that the fouling thermal resistance was lower on the surface with lower surface roughness, which was associated with the thickness of the fouling layer formed on the surface.